Effects of different conditioning activities performed after soccer-specific warm-up on post-activation performance enhancement - Alper Kartal; Muhammet Taha Ilhan; Esin Ergin; Zarife Pancar; Burak Karaca; Yasin Yildiz; Doğukan Batur Alp Gulsen; Serdar Bayrakdaroğlu (PLoS ONE, 2026)
The post-activation performance enhancement (PAPE) effect has been widely studied; however, studies conducted under real-world conditions remain limited. Furthermore, investigations into how different conditioning activities (CAs) influence PAPE responses are also scarce. Therefore, this study investigates the acute effects of high-intensity barbell hip thrust (BHT) and back squat (BS) exercises, performed after a soccer-specific warm-up (Wup), on physical performance in soccer players. Seventeen male amateur soccer players participated in the study (mean age: 22.29 ± 3.60 years; height: 1.78 ± 0.06 m; body weight: 73.18 ± 8.44 kg). Participants attended 5 experimental sessions. In the first session, after anthropometric assessments, participants were familiarized with the exercises and tests. In the second session, one-repetition maximum (1RM) was tested for BS and HT exercises. In the following three sessions, two PAPE protocols and one traditional (TRAD) protocol were performed in a randomized order. In the TRAD protocol, players performed physical performance tests including countermovement jump (CMJ), 10-m and 30-m sprint, and zigzag agility 16 minutes after a soccer-specific Wup. In the PAPE protocols, players performed CAs (e.g., hip thrust or back squat) at 85% of 1RM for 2 sets of 3 repetitions following a soccer-specific Wup, and completed the tests 8 minutes later. Results from the linear mixed-effects models revealed no significant effect of protocol on any performance variable, including CMJ (F(2,32) = 1.554, p = 0.227), 10 m sprint (F(2,32) = 0.242, p = 0.786), 30 m sprint (F(2,32) = 0.453, p = 0.640), and change of direction (COD) performance (F(2,32) = 0.946, p = 0.399). Marginal R² values indicated that the protocol explained only a minimal proportion of variance in performance outcomes (0.005–0.030), whereas conditional R² and ICC values suggested that between-participant differences accounted for a substantial proportion of variance, particularly for CMJ and 30 m sprint performance. Bonferroni-adjusted pairwise comparisons further showed no significant differences between PAPE BHT , PAPE BS , and TRAD protocols for CMJ, 10 m sprint, 30 m sprint, or COD performance (all p > 0.05). In conclusion, neither PAPE protocol performed after a soccer-specific warm-up significantly enhanced or impaired subsequent CMJ, sprint, or COD performance compared with the traditional warm-up. These findings suggest that adding PAPE BHT or PAPE BS protocols after a soccer-specific warm-up may maintain subsequent performance without inducing measurable decrements; however, their ergogenic effectiveness may depend on individual factors such as players’ strength levels, recovery capacity, training status, and physical characteristics.